Changements climatiques au Maghreb : vers des conditions plus humides et plus chaudes sur le littoral algérien ? - Zeineddine Nouaceur; Benoit Laignel; Imen Turki (Physio-Géo)
Significant climate changes affect a large part of our planet. The various models show an increase in rainfall and temperatures in many parts of the world. This research work analyzes the evolution of temperatures and rainfall recorded on the Algerian coast during more than forty years. The evolution of these two parameters reflects the recent climate upheaval experienced in recent years in North Africa and the Great Maghreb.